Financial awards and their effect on football players` anxiety and coping skills - Kaplánova, A. (Frontiers in Psychology, 2020)
Objective: Financial awards can be an important factor affecting athletes` mental preparation and various skills to manage stress. Since such a link has not yet been studied, the study has been designed to evaluate the moderation effect of financial awards in relation to football players` anxiety and coping skills.